The position of an athlete in sponsorship contacts regarding Olympic games - Jagodic, Tone (Array, 2020)
Sponsorship of individual athletes is not mainly based on intellectual industrial rights, but rather rests more on personal rights. As they are athletes involved in international competitions, they must adhere to the rules of various organisations. If an athlete wants to participate in Olympic Games, then s/he is obliged to respect the rules of IOC and NOC, and sign the Olympic Declaration which includes the code of suitability. Rule 40 of the Olympic charter is the key provision which must be respected throughout the Olympic Games. In Germany in the Bundeskartellamt (BKA)case of 2017, an administrative procedure was initiated against the German Olympic Sport Confederation and the IOC which revealed that the current application of rule 40 of the Olympic charter for athletes and sponsors in Germany limited competition and that DOSB andIOC are abusing their dominant position. The decision was based on the specific German legal context and does not apply to other jurisdictions. This means that the new rules ofDOSBin general are not applicable to other NOCs. DOSBandIOC proposed changes to their rules. IOC warned that widening new DOSB directions would threaten financial mechanisms of Olympic solidarity and the organisation of true global games with global participation. The pressure of top athletes, particularly from commercial sport, will grow and we can expect more intensive future discussions at both international and national levels. IOC and NOC will have to change the approach towards athletes on the one hand and not disregard the principle of solidarity towards most athletes who come from underdeveloped parts of the world and from not so media attractive sports.